Give them wings to fly: critiquing the Special Needs Assistant scheme through the lens of pupil independence. Issue 2 (15th March 2021) - Griffin, Claire; Blatchford, Peter
ABSTRACT: A significant increase in the paraprofessional workforce has occurred internationally, aimed at facilitating inclusive education. Within Ireland, this is evidenced in the SNA scheme for pupils with significant care needs. This paper focuses on the constructs of SNA support and pupil independence, as based on large-scale research across 20 Irish mainstream primary classes. The study was modelled on Strand 2 Wave 1 of the UK's 'Deployment and Impact of Support Staff' project, involving systematic observations and case studies. Following qualitative and quantitative analysis, findings serve to expand the construct of pupil independence beyond adaptive behaviour to include themes of pupil voice and psychological empowerment. The research also highlights both positive and negative educational practices to support pupil independence including SNA rotation, SNA–pupil proximity and prompting. Results are discussed in light of previous national and international research. Future directions of the SNA scheme are presented, including the potential of scaffolding theory to advance applied practices. Limitations of the research are acknowledged, including implications for research, theory, policy and practice. This research presents as the first Irish study to examine the SNA role using systematic observations, serving to extend existing research on the complex relationship between paraprofessional support and pupil independence.